Developmental asynchrony might not reduce fitness in early life in painted turtles - Colbert, P. L.; Spencer, R.-J.; Janzen, F. J. (Frontiers in Physiology, 2022)
Synchronous hatching and emergence of turtles from nests may be adaptive in predator avoidance during dispersal. However, little is known about the phenotypic consequences of such synchrony or the generality of predator avoidance in driving the evolution of this trait. Colbert et al. (2010) found that less advanced embryos hatched early in the presence of more advanced sibs, sustaining a persistent reduction in neuromuscular function. In this study, we experimentally assessed the influence of such accelerated embryonic development on hatching success, winter survival, and survival during terrestrial dispersal from the nest. Although we predicted that shortened incubation periods would reduce survival, early-hatching individuals suffered no detectable fitness costs at any stage considered in this study. Incubation temperature did not affect hatching success, and offspring sex did not affect survival across treatment groups. Incubation regime influenced offspring body size and was negatively correlated with dispersal time, however, there was no effect on survival during winter or terrestrial dispersal. Lack of a detectable fitness cost in these key early-life stages associated with hatching synchrony is consistent with a single, predator avoidance origin for this trait and retention in C. picta and other derived turtles via phylogenetic inertia.